SYSTEMATIC LITERATURE REVIEW: TRENDS AND EFFECTIVENESS OF TUTORIAL VIDEOS AS A PRACTICAL LEARNING MEDIUM - Usman, Usman; Marisa, Marisa; Surur, Miftahus (STKIP PGRI Situbondo, 2025)
This study aims to examine the trend in the use and effectiveness of video tutorials as a practical learning medium in various educational contexts. This literature review examines recent scientific publications (journals, proceedings, books) to investigate the trends, benefits, constraints, and research findings surrounding the effectiveness of video tutorials in improving the mastery of practical skills. A systematic literature review method was used to collect, filter, and analyze relevant studies published in recent years. The analysis results indicate an increasing trend in the use of video tutorials in practical learning, aligning with technological advancements and the growing demand for flexible and visual learning methods. Various studies report the effectiveness of video tutorials in improving conceptual understanding, procedural demonstrations, psychomotor skills, and student learning independence. However, several challenges, such as video production quality, limited direct interaction, and potential procrastination, were also identified. It is concluded that video tutorials are a potential and effective medium for practical learning. However, their implementation requires careful planning, appropriate instructional design, and integration with other learning strategies to achieve optimal results. Recommendations for further research and learning practices are also discussed.